PERAN DINAS PERHUBUNGAN KOTA BANDAR LAMPUNG DALAM MELAKSANAKAN PENGAWASAN KESELAMATAN PENGGUNA LALU LINTAS (Studi Di Dinas Perhubungan Kota Bandar Lampung) - bulan sueya ramadhani Bulan Surya Ramadhani Bulan; Eko Budi Sulistio (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
This study aims to examine the role of the Transportation Agency of BandarLampung City in supervising traffic safety and to identify the supporting andinhibiting factors. Using a qualitative descriptive method, the study found thattraffic safety supervision has been carried out through traffic monitoring, illegalparking control, ATCS-based monitoring, inter-agency coordination, andmaintenance of traffic facilities. Supporting factors include adequate facilities,effective personnel management, and good coordination, while inhibiting factorsinclude limited human resources, high traffic volume, and low public awareness oftraffic regulations. Therefore, strengthening supervision, optimizing technology,and increasing personnel and public awareness are necessary to enhance trafficsafety in Bandar Lampung City.